Numerical modelling of the one-dimensional diffusion by random walkers - Vamoş, C.; Suciu, N.; Peculea, M. (Rev. Anal. Numér. Théor. Approx., 1997)
In this paper we describe a numerical method of cellular automaton type to study the diffusion processes. The macroscopic diffusive behavior of a set of microscopic particles is obtained by the numerical simulation of particles motion as random walkers. We derive the averaging space-time scale needed for a macroscopical description of the diffusion process with a given precision. As an application we estimate the evacuation time by diffusion of a given number of particles from a fluid layer.